ANALYSIS OF THE INFLUENCE OF SEI MANGKEI SPECIAL ECONOMIC ZONE INFRASTRUCTURE ON THE ECONOMIC TRANSFORMATION OF SIMALUNGUN REGENCY - Feby Milanie; Abdiyanto; Ria Pratiwi Atmaja; Hasqiban Ritonga; Wahyu Rinaldi; Azura Cahaya; M.Arief Kurniawan; Dony Hardyansyah Pasaribu; Tesa Harefa (Bulletin of Engineering Science, Technology and Industry, 2026)
This study aims to analyze the impact of infrastructure development in the Sei Mangkei Special Economic Zone (SEZ) on economic growth in Simalungun Regency using a SWOT ( Strengths , Weaknesses , Opportunities , and Threats analysis method . The Sei Mangkei SEZ is a new economic growth center focused on the downstream palm oil and rubber industries . The primary focus of this study is to evaluate how the availability of supporting infrastructure — such as multimodal connectivity ( logistics) railways and toll roads ), dry port facilities , and energy independence — can drive the transformation of the region's economic structure from the primary sector ( raw agriculture ) to the secondary sector ( manufacturing ).